Calcitriol inhibits keratinocyte proliferation by upregulating leukocyte elastase inhibitor (serpin B1). Issue 5 (19th April 2014) - Hui, Li; Yongxia, Zheng; Zhili, Guo; Jun, Gu
Abstract Calcitriol had been proved to be effective for treatment of psoriasis vulgaris. However, the molecular events leading to the normalization of keratinocyte differentiation had not been fully explored. The aim of the study was to evaluate the role of calcitriol and serpin B1 in human keratinocyte cell line (HaCaT) proliferation. Proteins extracted from calcitriol‐treated and untreated HaCaT were separated by 2‐D differential gel electrophoresis (2DE). Then, the 2DE profiles were analyzed to screen for differentially expressed proteins, which were identified by matrix‐assisted laser desorption/ionization time of flight mass spectrometry. The upregulation of serpin B1 was confirmed by quantitative reverse transcription polymerase chain reaction (qRT–PCR) and western blot analysis. The effect of serpin B1 on HaCaT proliferation was analyzed by RNA interference experiments, methylthiazoletetrazolium assay and flow cytometry. Reproducible 2‐DE profiles of HaCaT were established. The result that serpin B1 was upregulated in the calcitriol‐treated group was confirmed by qRT–PCR and western blot analysis. Calcitriol could inhibit proliferation of HaCaT at the concentration of 10−9–10−6 mol/L. HaCaT proliferation was promoted when serpin B1 was interfered. The inhibition effect of calcitriol was stopped after serpin B1 was interfered. Serpin B1 was overexpressed in calcitriol‐treated HaCaT cells and may play an important role in inhibiting HaCaT proliferation by calcitriol.